Price audit of obtaining a weapons systems (Journal of the Spanish Institute for Strategic Studies, 2021)
The Spanish Ministry of Defence has achieved a saving of €429 million, as recorded in the last year’s report presented by the Cost Evaluation Group (GEC). This amount has been obtained by auditing contracts whose economic volume amounts to €6,209 million. In the last 13 years, the total savings achieved by the GEC amounts to more than €1,300 million. This remarkable progression has been achieved thanks to the increase in its means, the professionalisation of his members and to the fact that the GEC has equipped itself with its own internationally recognized methodology, for which it has been congratulated, especially during 2020, by various entities.The GEC was born in 1988 with the name of Cost Evaluation Working Group (GTEC), it is framed within the General Directorate of Economic Affairs of the Secretary of State for Defence and has carried out cost audits for international organisations such as NETMA (Nato Eurofighter and Tornado Management Agency) and OCCAR (Organisation for Joint Armament Cooperation, European intergovernmental organisation to facilitate and manage cooperative European Armament Programmes between France, German, Italy, United Kingdom and Spain) by having standards comparable to those of the most advanced countries of the European Union and NATO.
Keywords: Cost Evaluation Group, GEC, Life Cycle Cost, CCV, Savings, Audit, Market Price, Offer, Cost Analysis, Procurement Process, Weapon Systems, Cost Estimation, Company Rate, Price investigation.